2013
DOI: 10.1111/1750-3841.12212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rearing Conditions on the Microbiological Quality of Raw Retail Poultry Meat

Abstract: There is a gap in knowledge of microbiological quality in raw chicken products produced by nonconventional methods and no studies have reported the microbiological quality of turkeys produced under different rearing environments. Thus, the aim of this study was to compare the microbiological quality of conventionally and organically reared whole chicken and turkey carcasses purchased from 3 retail outlets in Knoxville, Tenn., U.S.A. A total of 100 raw broiler chickens organically (n = 50) and 50 raw turkey car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Our study did not identify any outbreaks associated with organic meats; however, studies suggest that meat produced under organic conditions might be more likely to be contaminated with foodborne pathogens than meat from conventionally produced animals (7,24). At the same time, because antimicrobial treatment is prohibited for organically raised animals, it has been found that organically produced meats have a lower prevalence of contamination with antimicrobial resistant bacteria (24).…”
Section: Discussioncontrasting
confidence: 58%
“…Our study did not identify any outbreaks associated with organic meats; however, studies suggest that meat produced under organic conditions might be more likely to be contaminated with foodborne pathogens than meat from conventionally produced animals (7,24). At the same time, because antimicrobial treatment is prohibited for organically raised animals, it has been found that organically produced meats have a lower prevalence of contamination with antimicrobial resistant bacteria (24).…”
Section: Discussioncontrasting
confidence: 58%
“…The recent increase in the consumption of organically raised poultry [ 30 ] due to the consumer assumption that organic poultry meat is of a better quality and more nutritious than the conventionally raised ones [ 31 ] raised concerns about the microbiological safety of organic meat. In a recent study in which the authors were trying to determine the impact of rearing conditions (conventional vs organic) on the microbiological quality of raw retail poultry, Campylobacter was highly prevalent on both rearing types and Salmonella was even higher under the organic rearing conditions [ 32 ]. The authors concluded that organic poultry should not be considered superior to conventionally produced one in relation to microbiological quality.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were developed using several different sources of information, including meetings with policymakers (MDA employees responsible for administering the Rabbit and Poultry On-Farm Processing Certification program), as well as informal conversations with three small poultry farmers in neighboring states who are professional contacts of the investigators. We also reviewed the existing food safety literature on the small-scale poultry supply chain [ 6 , 7 , 8 ], including the California study previously described [ 4 ] and the USDA-FSIS inspection criteria for poultry processing facilities [ 9 ].…”
Section: Methodsmentioning
confidence: 99%